Evaluating Kupferstein's claims of the relationship of behavioral intervention to PTSS for individuals with autism. Issue 3 (4th October 2018) - Leaf, Justin Barrett; Ross, Robert K.; Cihon, Joseph H.; Weiss, Mary Jane
Abstract : Purpose: Kupferstein (2018) surveyed 460 respondents and found that 46 percent of respondents met the diagnostic threshold for posttraumatic stress disorder after exposure to applied-behavior-analysis-based intervention. The purpose of this paper is to provide an evaluation a critical analysis of Kupferstein (2018) including the experimental methods and discussion of the results. Design/methodology/approach: The authors evaluated the Kupferstein's methodological rigor with respect to the use of hypothesis testing, use of indirect measures, selection of respondents, ambiguity in definitions, measurement system, and framing of the experimental question when conducting the correlational analysis in addition to Kupferstein's analysis and discussion of the results. Findings: Based upon the analysis, Kupferstein's results should be viewed with extreme caution due to several methodological and conceptual flaws including, but not limited to, leading questions used within a non-validated survey, failure to confirm diagnosis, and incomplete description of interventions. Originality/value: It is the authors' hope that this analysis provides caregivers, clinicians, and service providers with a scientific lens which will useful in viewing the limitations and methodological flaws of Kupferstein.